Pengaruh Keamanan Dan Kebersihan Makanan Terhadap Minat Beli Konsumen di Pasar Malam Korem Surabaya (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study is a quantitative research using an associative approach that aims to determine the influence of food safety and cleanliness on consumer purchase intention at the Korem Night Market in Surabaya. The respondents were consumers who had purchased food directly at the market, totaling 109 individuals, selected using the Slovin formula. The research instrument used was a closed-ended questionnaire with a Likert scale of 1–4 to measure respondents' perceptions of the variables studied. Validity and reliability tests were conducted to ensure the instrument’s feasibility. Data analysis techniques included classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results showed that both food safety (X₁) and food cleanliness (X₂) had a significant effect on consumer purchase intention (Y), both partially and simultaneously. The significance values in both the t-test and F-test were below 0.001, indicating strong and significant relationships. Moreover, the multicollinearity test results showed no symptoms of multicollinearity among the independent variables. Based on these findings, it can be concluded that food safety and cleanliness are two essential factors influencing consumers’ purchasing decisions in traditional markets.